The impact of public hearings on decision making on the merger of municipalities in the Moscow region - E. P. Shitova (Управление)
The practice of applying public hearings in the Moscow region in the transformation of municipalities for the period 2015-2018 has considered. In connection with changes in Russian legislation in recent years, public hearings have become an indispensable element of the interaction of citizens and municipal authorities when merging municipalities. The purpose of this article is to determine the actual influence of citizens, their opinions, suggestions made by them, the expression of consent or disagreement on the issue being considered at the hearing on the final decision. For this purpose, an analysis of the protocols and conclusions of public hearings has conducted, the main characteristics of this form of public participation in the implementation of local self-government have determined. Statistical data on the average number of participants in public hearings on the transformation of municipal districts into urban districts, time to prepare for them in the scale of 20 municipalities of the Moscow region, the results of citizens ’voting, the presence of representatives of state authorities and some other characteristics have provided. Also, a study of the arguments “for” and “against” the association has conducted, some contradictions in the points of view of representatives of the municipal government on the issues of transformations have identified. According to the results of the study, an assessment has made of public hearings as a form of democratic participation of citizens in the implementation of local self-government on the basis of its practical implementation in the Moscow region, and situations have identified in which the opinion of the population is able to correct the intended outcome of the changes. In particular, a conclusion has made about a fairly high percentage of citizens’ attendance at hearings, the absence in most cases of a unanimous opinion about the association of municipalities among citizens, and, on the contrary, a uniquely positive assessment of changes by the municipal government. It is also assumed that the most rare scenario - the abolition of the merger of municipalities under the influence of public hearings - is possible to a greater extent for rural settlements with a high initiative of the population.